Differentially expressed proteins confer thermotolerance in rooibos (Aspalathus linearis, (Burm.f.) R.Dahlgren) - MacAlister, Dunja; Rafudeen, Suhail; Gabier, Hawwa; Muasya, A. Muthama; Ogola, John B. O.; Ottosen, Carl-Otto; Rosenqvist, Eva; Chimphango, Samson B. M. (Acta physiologiae plantarum, 2025)
Aspalathus linearis (Burm.f.) R.Dahlgren, or rooibos, is an important commercial crop in the Western Cape, South Africa. The growth rate of rooibos is highest during the hot, dry summers typical for this region. This suggests that the plants have a wide range of adaptive responses including morphological, physiological, molecular, and biochemical mechanisms that help them cope with drought and heat stress. This study investigates differential expression of proteins in leaf samples harvested in summer from rooibos plants at two relatively cool, and two relatively hot sites in the Cederberg region. A total of 180 proteins were differentially expressed and of these, 113 proteins were more abundant at cooler sites while 67 proteins were more abundant at the heat-stressed (HS) sites. The higher temperatures at the HS sites led to a reduced protein abundance due to temperature thresholds for protein production during HS. Heat shock proteins were more abundant in the HS plants indicating an enhanced thermotolerance. Plants at the cooler sites overexpressed proteins associated with aiding photosynthesis and protecting photosystems, resulting in better photosynthetic rates and biomass accumulation. High light and moderate HS conditions prompted the regulation of proteins involved in chlorophyll synthesis and light protection to maintain effective functioning. Proteins involved in oxidative stress responses were expressed in plants at all sites, which was mirrored by high concentrations of antioxidants. Rooibos thermotolerance relies on the expression of HSPs and oxidative stress response proteins, while photosynthesis-related proteins dominate the cooler sites, optimizing their function and ultimately growth.